2016
DOI: 10.1002/wcc.397
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian estimation of climate sensitivity using observationally constrained simple climate models

Abstract: One‐dimensional simple climate models (SCMs) play an important role within a hierarchy of climate models. They have largely been used to investigate alternative emission scenarios and estimate global‐mean temperature change. This role has expanded through the incorporation of techniques that include Monte Carlo methods and Bayesian statistics, adding the ability to generate probabilistic temperature change projections and diagnose key uncertainties, including equilibrium climate sensitivity (ECS). The latter i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 83 publications
1
24
0
Order By: Relevance
“…Bayesian methods have recently been reviewed by Annan (2015) and Bodman and Jones (2016) and limitation by assuming constant sensitivity over time, the role of the ECSinf prior distribution and equal efficacy for different forcings have been discussed. Recently, studies have suggested that assuming equal efficacy for all forcings bias the ECS estimate low (Marvel et al, 2015;Shindell et al, 2015) even when ERFs are used (see also Appendix D).…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian methods have recently been reviewed by Annan (2015) and Bodman and Jones (2016) and limitation by assuming constant sensitivity over time, the role of the ECSinf prior distribution and equal efficacy for different forcings have been discussed. Recently, studies have suggested that assuming equal efficacy for all forcings bias the ECS estimate low (Marvel et al, 2015;Shindell et al, 2015) even when ERFs are used (see also Appendix D).…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian methods have recently been reviewed by Annan (2015) and Bodman and Jones (2016), and limitation by assuming constant sensitivity over time, the role of the ECS inf prior distribution and equal efficacy for different forcings have been discussed. Implementing an alternative prior for ECS inf as in Skeie14, where 1 / ECS inf is uniformly distributed, shifted the mean ECS inf to lower values from 2.0 • C (median 1.9 • C, 90 % CI 1.2-3.1 • C) to 1.6 • C (median 1.6 • C, 90 % CI 0.97-2.5 • C).…”
Section: Discussionmentioning
confidence: 99%
“…An additional problem arising from this is the resulting difficulty in synthesising estimates of climate system properties generated by different statistical methods with different, and often not explicitly introduced, assumptions. These methods include OLS but also alternative Bayesian approaches such as estimates of the climate sensitivity using energy-balance models Aldrin et al, 2012;Bodman and Jones, 2016).…”
Section: Introductionmentioning
confidence: 99%